(untitled) (Journal of Dhaka Medical College, 2025)
Diabetic striatopathy (DS) is an acute hyperkinetic movement disorder characterized by hemiballismus-hemichorea (HBHC) due to nonketotic hyperglycemia. Diabetic striatopathy occurs due to striatal (putamen, caudate nucleus, globus pallidus) pathology. The exact pathogenesis and mechanism remain unclear but may involve hyperviscosity, ischemia, and alterations in basal ganglia neurotransmitters. We present here a case of HBHC syndrome with right-sided neuroimaging findings and contralateral chorea due to uncontrolled type 2 diabetes mellitus. She had a history of poorly controlled type 2 diabetes and presented with involuntary movements of her left limb suggestive of chorea. Laboratory tests confirmed hyperglycemia, with an elevated hemoglobin A1c level. Neuroimaging revealed T1-hyperintensity in the right putamen. The patient was diagnosed with diabetic striatopathy and responded well to insulin therapy and haloperidol with a rapid resolution of symptoms. The striking features on imaging such as computed axial tomography (CT) scan of the brain and T1-weighted magnetic resonance imaging (MRI) of the brain can mislead the clinician to an erroneous diagnosis of a cerebral hemorrhage and/or ischemic infarct, especially in an acute setting. With careful and thoughtful analysis, an accurate diagnosis can spare the patient unnecessary anxiety and medical costs. J Dhaka Med Coll. 2024; 33(1) : 42-46